Optimum dosage of a new preemergence herbicide oxifluorfen (Commercial name GOAL) on the cassava planted in different soil types - Kano, Y; Leihner, D.E. (International Center for Tropical Agriculture, 1978)
The main objectives of this expt. were to study the optimum dosage of the preemergence herbicide, oxyfluorfen, on different soil types by evaluating the chemical injury on cassava leaves; investigate the relationship between the diameter of the cutting and the initial growth; analyze aspects of mineral nutrition of N- deficient plants; and obtain general information about the effect of urea leaf application to these plants. Injury by the herbicide increased with increasing application of oxyfluorfen; as soil content increased and clay content decreased, herbicide damage increased. These was no correlation of the diameter of the cutting to the germination rate or plant height. Fifty days after planting, the upper leaves of some plants showed N deficiency. Leaf application of 1 and 2 percent urea caused damage at the same degree of severity. (CIAT)